The Impact of Eco-economic Policies on Financing Costs of Smes: The Regulatory Effects of Green Credit Mechanisms - Liu, Can (International Journal of Global Economics and Management, 2024)
Driven by the global ecological environment deterioration and sustainability agenda, ecological economic strategy has increasingly highlighted its key role in green transformation. As a crucial component of the economic system, small and medium-sized enterprises are inevitably subjected to increasing environmental protection challenges and capital access problems while promoting economic growth. This paper aims to explore the impact of ecological economic policies on the financing costs of smes, and further analyze the regulatory role of green credit mechanism. Based on the research of international and domestic related literature in recent years, this study refined the diversity of ecological economic policies and the double potential effects of these policies on the acquisition cost of development capital of small and micro enterprises, with both possible positive and potential negative sides. Under this theoretical framework, we set the corresponding research hypothesis. In order to deeply analyze this issue, this paper adopts a quantitative analysis strategy, relying on the specific case data of small and medium-sized enterprises in China, and uses a multivariate regression model to verify the interaction between ecological economic policies and corporate financing costs. At the same time, we introduce the green credit system as a moderator, so as to reveal its mediating influence mechanism in the above relationship.